2021
DOI: 10.1007/s40121-021-00480-0
|View full text |Cite|
|
Sign up to set email alerts
|

Budget Impact Analysis of Fidaxomicin Versus Vancomycin for the Treatment of Clostridioides difficile Infection in the United States

Abstract: Introduction: Fidaxomicin is as effective as vancomycin in treating Clostridioides difficile infection (CDI) but more effective at preventing recurrence. However, because fidaxomicin is more costly than vancomycin, its overall value in managing CDI is not well understood. This study assessed the budget impact of introducing fidaxomicin versus vancomycin for the treatment of adults with CDI from a hospital perspective in the US. Methods: A cohort-based decision analytic model was developed over a 1-year horizon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Given the differences in healthcare systems, it is difficult to compare the per patient cost in Germany for fidaxomicin to the PMPM cost of FMBL in the US; however, both models showed that higher drug costs were offset by the reduction in medical costs associated with rCDI. A recent US model by Jiang et al [29] was developed from a hospital perspective and demonstrated a minimal budget impact of fidaxomicin in the US. In addition, two prior studies evaluated the budget impact of bezlotoxumab plus antibiotics compared to antibiotics alone in patients for the prevention of recurrence from a hospital perspective in Germany and the US, respectively [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Given the differences in healthcare systems, it is difficult to compare the per patient cost in Germany for fidaxomicin to the PMPM cost of FMBL in the US; however, both models showed that higher drug costs were offset by the reduction in medical costs associated with rCDI. A recent US model by Jiang et al [29] was developed from a hospital perspective and demonstrated a minimal budget impact of fidaxomicin in the US. In addition, two prior studies evaluated the budget impact of bezlotoxumab plus antibiotics compared to antibiotics alone in patients for the prevention of recurrence from a hospital perspective in Germany and the US, respectively [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…This narrow spectrum of activity results in superiority over vancomycin with regard to recurrence/sustained clinical response up to 25 days after treatment completion (Louie et al 2011;Cornely et al 2012); however, it has been reported as inferior to vancomycin for clinical response to RT 027 infections (Louie et al 2011;Cornely et al 2012). Its high cost (USD1 767 for 10 day treatment) initially raised concerns about its benefit compared with treatment with vancomycin (USD14) or metronidazole (USD8), but multiple cost effectiveness analyses demonstrated that it is cost effective due to high cure rates and prevention of recurrent episodes, reducing re-admissions to hospital (Rajasingham et al 2020;Jiang et al 2021).…”
Section: Treatment Of Initial and Recurrent Episodes Of CDImentioning
confidence: 99%
“…In brief, antibiotic treatment is still considered as a cornerstone of CDI treatments, and there still is an unmet medical need for new antibiotics that could further reduce the recurrence rate. , Moreover, vancomycin and fidaxomicin exhibit diminished activity against the emerging hypervirulent strain of C. difficile ribotype 027. Therefore, a new prospective agent in CDI shall not cause a significant dysbiosis and has an elevated activity against ribotype 027.…”
Section: Introductionmentioning
confidence: 99%